Songs as Transformative Ideology: An Ethnomusicological Approach to the Song Hai Tanahku Papua at GKI in Papua Land - Wompere, Oskar Ayub; Setyawan, Yusak; Y.M. Lattu, Izak; Listya, Agastya Rama (International Journal of Educational Research Excellence (IJERE), 2024)
The purpose of this research is to analyze nyayian as a transformative ideology that focuses on the ideas of the song Hai Tanahku Papua. The song can be an ideological song that can lead listeners to experience life as Papuan people. The research method used in this study is qualitative research with descriptive analysis usingEthnomusicological Approachwith data collection techniques using observation, interview and documentation methods on Papuan people who live in the GKI Tanah Papua church. From the results of the study, the author found that singing is one of the transformative ideologies of Papuan people in living life as a society.The ideology conveyed through songs with theological nuances for Papuans is a warning and message in the form of loyalty, obedience and listening to God which can determine success in the land of Papua. Ethnomusicology must enter to be able to provide the right answer through cultural and musical solutions from different perspectives while bridging renewal for social justice for all Indonesian people on the land of Papua.